PSIV-B-27 Effect of feed flavour on the feeding behaviour and kinetics of daily feed intake of lactating high-prolific sows during summer. (8th October 2021) - Silva, Bruno Alexander N; Eskinazi, Simon; Jacob, David V; Araújo, Wagner; Ataíde, Iara; Evangelista, Rafaela; Motta, Stephane A; Rebordoes, Flavio Igor G; Araújo, Dalton; Cardoso, Larissa A; Habit, Steve; Gonçalves, Mateus F; et al.
Abstract: Increasing voluntary feed intake of the sow is a major challenge for nutritionists in tropical climate conditions. The present study aimed to evaluate the impact of the dietary supplementation of a feed flavour for sows during lactation on their feeding behavior and kinetics of daily feed intake under tropical conditions. A total of 60 high-prolific mixed parity sows divided into 10 batches of 6 sows each were used, distributed in a completely randomized experimental design among 2 dietary treatments (0 or 500 g/ton of Krave®, Adisseo). The average meal size was 107 g/meal lower in sows fed the control diet when compared with flavour fed sows. Daily feed intake was greater in the flavored diet than in the control (6, 417 vs. 5, 362 g/d; P < 0.05). The flavor improved ingestion time (58.4 vs. 46.6 min/ d, respectively flavour and control; P < 0.05). Sows receiving flavor showed a higher nocturnal (704 vs. 583 g/meal) and diurnal (678 vs. 582 g/meal) feed intake. Sows also showed a higher voluntary intake between 00:00 and 10:00 am, which was equivalent to 83% of the total daily feed intake. From a comparison of hourly feed intakes or variations from hour to hour (during 24 h), the nycthemeral pattern of feed intake peaked twice daily for both dietary treatments. However, the size of the peak was greater (P < 0.05) for flavour fed sows when compared with the control at 0400 and 1900 h (Figure 1a). Diets also influenced on kinetics of daily feed intake during the lactation period.Feed intake was higher for the flavour fed sows from d 3 to 8 and from d 10 to 24 (Figure 1b; P < 0.05).In conclusion, the strategic use of a feed flavour to manipulate the sensorial properties of feed is a viable strategy to increase the sows' voluntary feed intake.